2016
DOI: 10.5114/pdia.2016.56928
|View full text |Cite
|
Sign up to set email alerts
|

Effects of isotretinoin on body mass index, serum adiponectin, leptin, and ghrelin levels in acne vulgaris patients

Abstract: IntroductionIsotretinoin has been successfully used for the treatment of acne vulgaris.AimTo investigate the effects of isotretinoin on body mass index (BMI), to determine whether isotretinoin causes any changes in serum adiponectin, leptin, and ghrelin levels in acne vulgaris patients, and to correlate variables.Material and methodsThirty-two patients were included in this study. Oral isotretinoin was begun at a dose of 0.5–0.6 mg/kg and raised to 0.6–0.75 mg/kg. Pretreatment and posttreatment third-month BMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 45 publications
2
18
0
1
Order By: Relevance
“…In the past, nutrition was not a proven cause of acne. However, recent publications show a link between some dietary factors and acne . Nowadays, main food classes considered triggering acne are dairy products (especially skim milk) and hyperglycaemic carbohydrates …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, nutrition was not a proven cause of acne. However, recent publications show a link between some dietary factors and acne . Nowadays, main food classes considered triggering acne are dairy products (especially skim milk) and hyperglycaemic carbohydrates …”
Section: Resultsmentioning
confidence: 99%
“…However, recent publications show a link between some dietary factors and acne. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Nowadays, main food classes considered triggering acne are dairy products (especially skim milk) and hyperglycaemic carbohydrates. 10,[29][30][31][32][33][34][35][36][37] An average regimen of dairy products has been reported impacting on acne, and one paper indicated that cow milk impacts on acne after already two glasses per day.…”
Section: Acne Exposome Factorsmentioning
confidence: 99%
“…Назначение изотретиноина в классических дозах (0,5 мг/кг/сут) сопряжено с обширным диапазоном неблагоприятных, но легко прогнозируемых побочных эффектов, вызывающих некоторый дискомфорт. Наличие противопоказаний к назначению классических доз значительно ограничивает возможности применения при сопутствующей соматической патологи [37][38][39][40][41]. В настоящее время прием изотретиноина в дозе 0,5-1 мг/кг/сут является противопоказанием к параллельному проведению косметологических и лазерных процедур, направленных на раннюю профилактику и коррекцию симптомокомплекса постакне (рубцы, застойные пятна, гиперпигментация) в период приема и в течение 6-12 мес после завершения курса лечения [42][43][44][45].…”
Section: изотретиноинunclassified
“…It is known that one of the mechanisms by which isotretinoin exerts its activity is by increasing the leptin levels during and after therapy. 17 Leptin, which is encoded by LEP gene, 18 is an important adipokine that plays important roles in appetite pathway 19 and energy expenditure via the regulation of lipid and sugar metabolism. 20 , 21 Literature also showed that leptin protein is elevated during skin diseases, which suggests a role for leptin in immune network and body defenses.…”
Section: Introductionmentioning
confidence: 99%